NEGOSIASI SEBAGAI UPAYA PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL - Tinangon, Edwin Neil; Sinaga, Thor Bangsaradja; Mangowal, Mario Gerson (Legal Standing : Jurnal Ilmu Hukum, 2024)
This research discusses the implementation of negotiations in the settlement of industrial relations disputes in North Minahasa Regency. The main focus lies on the legal regulation of negotiation according to Law No. 13 of 2003, Law No. 2 of 2004 on Industrial Relations Dispute Resolution, and Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution. The research uses a normative juridical method, namely an approach carried out using legal materials by examining theories, concepts, legal principles and related laws and regulations. The goal is to understand, analyze existing legal norms. This method tries to find what should be done according to a set of norms or values. both written, and unwritten and analytical descriptive research, namely describing the applicable laws and regulations associated with legal theory and the practice of implementing positive law in society. By using this method, it will be known the significant relationship between the variables studied so as to clarify the object under study. The results showed that in North Minahasa, negotiation is very useful in every community problem. As a form of communication to reach an agreement, negotiation is not only done by two parties, but can be done by several parties. Through negotiation, the parties can reach an agreement, including playing an important role in the settlement of industrial relations disputes. In every industrial relations dispute, settlement must first be sought through bipartite negotiations between workers/laborers or trade unions/laborers and employers, in a deliberative manner to reach consensus before entering into litigation. Strategies to increase the effectiveness of negotiations involve an interest-based approach, trust between parties, the role of mediators, and negotiation skills training. This aims to create a win-win solution and avoid time-consuming and costly legal proceedings.